2021
DOI: 10.3390/molecules26134096
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects of Lithium Salts with Various Anionic Species in Poly (Methyl Methacrylate)

Abstract: We report that lithium salts in lithium-ion batteries effectively modify the physical properties of poly (methyl methacrylate) (PMMA). The glass transition temperature (Tg) is an indicator of the heat resistance of amorphous polymers. The anionic species of the salts strongly affected the glass transition behavior of PMMA. We focused on the additive effects of various lithium salts, such as LiCF3SO3, LiCOOCF3, LiClO4, and LiBr, on the Tg of PMMA. The large anions of the former three salts caused them to form m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
(44 reference statements)
3
9
0
Order By: Relevance
“…The mean relaxation time < τ F > in the flow zone for PMMA/Li-salts with the salt concentration at 0.07 mol/mol was estimated to be 0.40 s for PMMA, 0.63 s for PMMA doped with LiCF 3 SO 3 , and 180 s for PMMA doped with LiBr 13,20) . PMMA doped with LiBr shows a much longer < τ F > value than those of the pristine PMMA and PMMA/ LiCF 3 SO 3 .…”
Section: Effects Of the Anion Size On Glass Transition Behaviormentioning
confidence: 98%
See 4 more Smart Citations
“…The mean relaxation time < τ F > in the flow zone for PMMA/Li-salts with the salt concentration at 0.07 mol/mol was estimated to be 0.40 s for PMMA, 0.63 s for PMMA doped with LiCF 3 SO 3 , and 180 s for PMMA doped with LiBr 13,20) . PMMA doped with LiBr shows a much longer < τ F > value than those of the pristine PMMA and PMMA/ LiCF 3 SO 3 .…”
Section: Effects Of the Anion Size On Glass Transition Behaviormentioning
confidence: 98%
“…An increase in T g was observed for these salt-doped samples. In addition, the infrared (IR) spectra of these samples suggest that ion-dipole interaction develops between the lithium cations and carbonyl groups of PMMA chains; moreover, these samples maintain a transparency above 80 % even under a salt ratio of 0.07 mol/mol 13) . Miyagawa et al reported that the transmittance of PMMA-salt complexes remains at approximately 90 % even over a salt ratio of 70 wt% 9) , so adding some lithium salts does not impair PMMA transparency.…”
Section: Effects Of Non-free Ion Frac-tion On Glass Transition Behaviormentioning
confidence: 99%
See 3 more Smart Citations